Uplifting Local Wisdom in Soil and Water Conservation System - Utari Utari; Syazarah Soraya; Yuni Wulandari (Education Achievement: Journal of Science and Research, 2024)
The environmental conditions significantly influence the quality of life for humans and other living beings, thus requiring attention to robust and consistent environmental protection and management conditions by all stakeholders. Various principles are utilized in environmental protection and management, and one of these principles is culture and local wisdom. Local wisdom comprises noble values applied in the community's way of life, including, among other things, sustainable protection and management of the environment. Protection and management of the environment must also consider the noble values prevailing in the community's way of life. The occurrence of a water crisis resulting from the reduction of water sources and the weakened conditions of living organisms is due to the insufficient attention to the rules of local wisdom. Various efforts have been made for soil and water conservation, both by the government and environmentalists. The management of water and soil resources is not only the responsibility of the government outlined in various written policies but also the responsibility of the local community evident in the knowledge and experience of the community in carrying out various water and soil management activities.